PENGARUH INDEPENDENSI DAN EFEKTIVITAS KOMITE AUDIT TERHADAP MANAJEMEN LABA PADA PERUSAHAAN FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Anto, La ode; Dharmawati, Tuti; Vinarti, Wa Ode Juni (JURNAL AKUNTANSI DAN KEUANGAN, 2017)
This study aims to see the Effect of Independence and Effectiveness of the Audit Committee Against Profit Management On Pharmaceutical Companies Listed in Indonesia Stock Exchange (IDX).The sample in this study is a pharmaceutical company listed on the Indonesia Stock Exchange period 2010-2015. The sampling technique in this study using purposive sampling method sampling method adapted to criteria-specific criteria. The results of this study showed that simultaneous independence and effectiveness of the audit committee but not significant negative effect on earnings management. Partially independence of the audit committee but not significant negative effect on earnings management, audit committee effectiveness begipula no significant negative effect on earnings management. Keywords: Independence, Audit Committee Effectiveness and Profit Management.